Arabidopsis PIAL1 and 2 Promote SUMO Chain Formation as E4-Type SUMO Ligases and Are Involved in Stress Responses and Sulfur Metabolism . Issue 11 (18th November 2014) - Tomanov, Konstantin; Zeschmann, Anja; Hermkes, Rebecca; Eifler, Karolin; Ziba, Ionida; Grieco, Michele; Novatchkova, Maria; Hofmann, Kay; Hesse, Holger; Bachmair, Andreas
Abstract : Substrates modified by covalent attachment of the small ubiquitin-related modifier (SUMO) usually receive a single SUMO moiety. Existence of enzymes that promote formation of SUMO chains indicates that such chains have distinct roles in plants, and mutant analysis indicates involvement in regulation of sulfur metabolism and stress responses. Abstract: The Arabidopsis thaliana genes PROTEIN INHIBITOR OF ACTIVATED STAT LIKE1 ( PIAL1 ) and PIAL2 encode proteins with SP-RING domains, which occur in many ligases of the small ubiquitin-related modifier (SUMO ) conjugation pathway. We show that PIAL1 and PIAL2 function as SUMO ligases capable of SUMO chain formation and require the SUMO -modified SUMO -conjugating enzyme SCE1 for optimal activity. Mutant analysis indicates a role for PIAL1 and 2 in salt stress and osmotic stress responses, whereas under standard conditions, the mutants show close to normal growth. Mutations in PIAL1 and 2 also lead to altered sulfur metabolism. We propose that, together with SUMO chain binding ubiquitin ligases, these enzymes establish a pathway for proteolytic removal of sumoylation substrates.